Analysis of Electoral Fraud and its Alternative Efforts: a case study in banguntapan: Analisis Kecurangan Pemilu dan Upaya Alternatifnya: studi kasus di Banguntapan - Mohammad Jailani (Senarai: Journal of Islamic Heritage and Civilization, 2024)
The occurrence of fraud, injustice, and dishonesty in the validation of election data by the Election Team and Committees from villages to the capital city. This happens everywhere, caused by the competition for popularity and tight competition among the different camp teams. Therefore, researchers intend to investigate the occurrence of election fraud in 2019. This research aims to identify the problems of election fraud and valid election data, especially in the Special Region of Yogyakarta in the Wirokerten area, Banguntapan Bantul. The setting of this research is in the Wirokerten area of Banguntapan Bantul Yogyakarta. The subjects of this research consist of village heads, election committee teams, potential voters, former voters in 2019, and local communities. The selection of research subjects is carried out with honesty and data validity. It means researchers have directly asked and met directly with informants or research subjects. Research subjects are selected based on gender perspective and informant character. This research is qualitative, a type of case study research, namely the case of the 2019 election and the upcoming 2024 election. Data is collected through direct interviews and direct observation at the location. "including researchers and local residents located in Mutihan, Wirokerten Banguntapan, Bantul Yogyakarta". Data analysis is carried out with reference to previous theories as proposed by Miles and Huberman (reduction, display, and verification). The research results indicate the existence of fraud and lack of clarity in the calculation of the 2019 election due to a lack of information and communication from the election team to the village level, such as village heads and subdistrict heads. Lack of supervision and not using IT/applications related to election vote counting. Based on the information data, there are 4-5 ballot boxes that have not been delivered; there is the incapacity of the election team or permission due to illness during the election event. 80% of problems exist in DIY indicating electoral disputes. Therefore, researchers respond well to alternatives provided by researchers as a valid, credible, and transparent prototype election strategy for 2024